ATTITUDES OF MEMBERS OF THE UNIVERSITY SPORTS DEPARTMENT TOWARDS ORGANIZING STUDENT SPORTS ACTIVITIES AT AL-QADISIYAH UNIVERSITY - Dr. Abdul-Hussein Majid Mohammad (Proximus Journal Publishing, 2024)
The spirit of the members of the sports faculty in a university has a major role in intellectual development in all fields (and more especially on the sports field). For this reason, interest was kindled in an introspective attitude because it is a complex mental quality comprising cognition and also related to emotional and behavioural components toward a particular topic.
Keywords: Psychological orientation; University sports activities; Attitudinal measurement